Amyloids as Biomineralizing Tools - Gasset, M. (2019)
BIOMATSEN 2019, Oludeniz/Mugla - Turkey, May 12-18, 2019. -- INVITED SPEAKERS BACKGROUND: Design and production of materials to suffice the world demands with an eco-friendly view is essential for the construction of a sustainable planet. Bioinspiration provides a uniquely safe strategy, putting synthetic biology at a leadership position. Of the distinct biocomposites, calcium carbonate biominerals forming balancing systems and shells are the most abundant. In these biominerals, the nucleation, growth and morphology of carbonate crystals are modulated by acid proteins. These proteins also share oligomerization propensity involving extended ß-strand structures, suggesting that amyloid assemblies with acidic regions could modulate calcium carbonate crystallization. OBJECTIVE: To test whether amyloid folds of biocomposite unrelated Ca2+-binding proteins influence calcium carbonate crystallization in vitro. RESULTS: Gad m1, an Atlantic cod ß-parvalbumin isoform was produced recombinantly and assembled into amyloids by Ca2+ removal. Atomic force microscopy showed protofibrillar or rod-like nanoplatelet assemblies. After verifying their stability, the assemblies were placed in the presence of Ca2+ and calcium carbonate precipitation was enabled by controlled diffusion of CO2 from the decomposition of ammonium carbonate. The representative crystal structures that formed were visualized by scanning electron microscopy. Controls for the absence of protein and presence of soluble Gad m 1 monomer yielded the common rhombohedral form of calcite crystals. In contrast, amyloids yielded cylindrical and sheaf-like calcite crystals as judged by their selected area electron diffraction patterns. SIGNIFICANCE: These results provide a proof of concept for the functional exploitation of a non-physiological amyloid in the field of calcium carbonate-based materials.